GR-coated TA-Ag-coated MIH electrode modification material and application thereof
By using GR@TA-Ag@MIH electrode modification materials and molecular imprinting technology, the problem of expensive equipment for methyl parathion detection methods in the prior art is solved, with long analysis time and insufficient detection accuracy, and high sensitivity, specificity and cost-effective detection effects are achieved.
Patent Information
- Application Number
- CN202411830470.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The methods used for methyl parathion detection in the prior art have problems such as expensive equipment, long analysis time, complex sample preprocessing, and insufficient detection accuracy and specificity.
GR@TA-Ag@MIH electrode modification material is used to react with a composite material composed of graphene, tannin and silver ions with a mixed solution of acrylamide and ammonium persulfate to form a hydrogel electrode. Combined with molecular imprinting technology, high specific identification of methyl parathion is achieved.
It significantly improves the detection sensitivity and stability of methyl parathion, achieves high accuracy and specific detection of methyl parathion, and has low equipment cost, simple sample pre-processing and short analysis time.
Smart Images

Figure CN119708312A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of food safety detection, and in particular to a GR@TA-Ag@MIH electrode modification material and application thereof. Background Art
[0002] Parathion-methyl (MP) is an organic compound with the chemical formula C8H 10 NO5PS is a highly toxic, highly effective, broad-spectrum organophosphorus insecticide. Methyl parathion (MP) has a series of advantages such as high efficiency, broad spectrum, small dosage, multiple modes of action, easy use, and short half-life. It has been widely used in agricultural production and has played an important role in the prevention and control of various diseases and pests on many crops. However, methyl parathion degrades slowly in the natural environment, and there will be a large amount of residue, causing serious pollution and harm to the ecological environment. It can also be enriched in the human body through the food chain, thereby causing various diseases and endangering human physiological health. Therefore, methyl parathion is banned in many countries, and is also strictly regulated in the import and export trade of agricultural products and food safety management. Therefore, it is crucial to construct a rapid detection method for the detection of methyl parathion.
[0003] At present, the traditional separation and analysis methods reported in the literature for methyl parathion mainly include chromatography and chromatography-mass spectrometry for qualitative and quantitative detection. However, the equipment used in the above detection methods is expensive, the analysis time is long, and complex sample pretreatment technology is required; therefore, it is of great significance to develop a fast, accurate and sensitive detection method for methyl parathion. From the structure of methyl parathion, it can be seen that methyl parathion contains a nitro group, which means that methyl parathion is an electrochemically active substance, so it can also be directly determined by electrochemical methods.
[0004] In the document "Development of molecularly imprinted electrochemical sensor for methyl parathion based on graphene sensitization.", Wu Jiawen et al. used the graphene-sensitized molecularly imprinted electrochemical sensor for methyl parathion based on graphene sensitization to detect the organophosphorus pesticide methyl parathion. The nanomaterial graphene was combined in the preparation of the molecularly imprinted sensor to effectively improve the analytical performance of the sensor. However, when detecting structural analogs such as chlorpyrifos, triazophos, and phoxim, there was also a current response, which would reduce the accuracy of the detection result. Patent CN118746607A discloses a molecularly imprinted photoelectrochemical sensor for methyl parathion and a preparation method thereof. The photoelectrochemical sensor includes a reference electrode, a saturated calomel electrode, and a working electrode. The working electrode is a molecularly imprinted electrode. The molecularly imprinted electrode includes a conductive substrate and a composite material (Bi2WO6QDs / flower-like COF) loaded on the conductive substrate. Bismuth tungstate quantum dots are used to cooperate with flower-like COF to increase the charge conversion capacity and improve the separation efficiency of electron-hole pairs. However, the synthesis process of its electrode modification material Bi2WO6QDs / flower-like COF is relatively complicated, and it also requires high temperature and high pressure reaction. In addition, it has not explored its selectivity for other compounds with similar structures in depth. However, the recognition sites of traditional MIPs are unevenly distributed, and some sites may be deeply buried inside the polymer, resulting in reduced recognition efficiency, and easy to fall off on the electrode surface, with poor mechanical strength, affecting the stability of the sensor, thus causing the sensitivity and reproducibility of molecular imprinting polymer-modified electrochemical sensors to detect methyl parathion to deteriorate. Summary of the invention
[0005] In view of the above-mentioned prior art, the purpose of the present invention is to provide a GR@TA-Ag@MIH electrode modification material and application thereof.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] In a first aspect of the present invention, a GR@TA-Ag@MIH electrode modification material is provided, which is prepared by the following method:
[0008] (1) Dissolve tannic acid (TA) in deionized water, add Tris solution to adjust the pH to 7.5-8.5, then add AgNO3 and stir to obtain TA-Ag solution;
[0009] (2) dissolving graphene (GR) in TA-Ag solution to form GR@TA-Ag suspension;
[0010] (3) The GR@TA-Ag suspension was added to a mixed solution containing acrylamide (AM), ammonium persulfate (APS) and methyl parathion (MP), stirred for 5-15 minutes, and washed after the reaction to obtain the GR@TA-Ag@MIH electrode modified material.
[0011] Preferably, in step (1), the ratio of the added amount of tannic acid to that of deionized water is (1-3) mg: (0.5-1.5) mL; and the concentration of the Tris solution is 0.8-1.5 M.
[0012] Preferably, in step (1), the mass ratio of AgNO3 and tannic acid is (1-3): (1-3).
[0013] Preferably, in step (2), the material-liquid ratio of graphene and TA-Ag solution is (3-5) mg: (0.5-1.5) mL.
[0014] Preferably, in step (3), the volume ratio of the GR@TA-Ag suspension and the mixed solution is (1-3): (1-3).
[0015] Preferably, in step (3), in the mixed solution, the mass percentage of acrylamide is 15-25%; the mass percentage of ammonium persulfate is 0.1-0.3%; and the mass percentage of methyl parathion is 0.002-0.004%.
[0016] Preferably, in step (3), the specific method of washing is:
[0017] The methyl parathion was first eluted with a mixed solution of methanol and acetic acid and then washed with deionized water.
[0018] Preferably, in the mixed solution of methanol and acetic acid, the volume ratio of methanol to acetic acid is (7-9):(1-3).
[0019] The second aspect of the present invention provides the use of the above-mentioned GR@TA-Ag@MIH electrode modification material in the preparation of an electrochemical sensor for detecting methyl parathion.
[0020] In a third aspect of the present invention, an electrochemical sensor is provided, wherein the electrochemical sensor uses a glassy carbon electrode modified with the GR@TA-Ag@MIH electrode modification material as a working electrode, a platinum electrode as an auxiliary electrode, and a saturated calomel electrode as a reference electrode.
[0021] Preferably, the working electrode is prepared by the following method:
[0022] The GR@TA-Ag@MIH electrode modification material was drop-coated onto the surface of the bare glassy carbon electrode using a syringe and allowed to dry to obtain a modified GR@TA-Ag@MIH@GCE electrode, which was the working electrode.
[0023] A fourth aspect of the present invention provides a method for detecting methyl parathion using the above electrochemical sensor, comprising the following steps:
[0024] (1) The working electrode, reference electrode and auxiliary electrode in the electrochemical sensor constitute a three-electrode system. The working electrode is immersed in different concentrations of methyl parathion standard solution and incubated in the potential window range of -0.6 to 0.1 V using differential pulse voltammetry, and the corresponding current value I is recorded. P ; With the concentration of methyl parathion standard solution as the abscissa and the current value I as the ordinate, draw a working curve;
[0025] (2) Using the working curve drawn in step (1), the content of methyl parathion in the pre-treated analyte is detected.
[0026] Preferably, in step (2), the pretreatment method of the analyte is: repeatedly extracting the analyte with acetonitrile by vortex centrifugation for 2 to 4 times, promoting the separation of the aqueous phase and the organic phase with sodium chloride, combining the extracts and drying them with nitrogen, dissolving the residue obtained after nitrogen blowing with phosphate buffer solution, and filtering to obtain the sample extract.
[0027] More preferably, the ratio of the added amount of the analyte to acetonitrile is 1 g: (1-5) mL.
[0028] Beneficial effects of the present invention:
[0029] (1) The present invention uses a GR@TA-Ag@MIH modified electrode as a working electrode and successfully constructs an electrochemical sensor capable of sensitively detecting methyl parathion. Among them, the graphene in the GR@TA-Ag@MIH composite material gives the sensor excellent conductive properties, and the introduced metal ions further enhance the conductive properties of the composite material. Through molecular imprinting technology, the sensor achieves highly specific recognition of methyl parathion, effectively avoiding the oxidation peak interference of structurally similar compounds at the same potential, thereby significantly improving the accuracy of detection; the electrochemical sensor of the present invention is inspired by mussels and uses a dynamic dual catalytic system to promote the rapid polymerization of free radicals to form a hydrogel, and constructs a TA-Ag dual catalytic system. The catechol group on TA can reduce silver ions to silver nano-ions, and is converted into semiquinone or quinone groups through oxidation of silver ions; the corresponding semiquinone or quinone groups and silver ions activate APS to generate sulfate radicals, thereby accelerating the free radical polymerization of acrylamide monomers without the need for external energy. When the GR@TA-Ag suspension was added to a mixed solution containing acrylamide (AM), ammonium persulfate (APS) and methyl parathion (MP), the free radical polymerization of acrylamide monomer was promoted, so that the formation of hydrogel did not require high-temperature heating, and the free radicals polymerized rapidly at room temperature; combined with molecular imprinting technology, the hydrogel had the ability of specific recognition, realizing the specific recognition of methyl parathion; combining hydrogel with molecular technology solved the problems of poor compatibility, easy shedding and long synthesis process of existing molecular imprinting sensors; the combination of the above multiple advantages significantly improved the oxidation peak current value of methyl parathion, giving the sensor higher sensitivity and stability.
[0030] (2) The minimum detection limit of methyl parathion using the electrochemical sensor of the present invention is 0.1 umol / L; the MRL value of methyl parathion stipulated in the national standard is 0.2 mg / kg. Therefore, the present method can meet the detection needs. In addition, the electrochemical sensor prepared by the present invention has low cost, simple pretreatment, high sensitivity, short analysis time, and simple experimental operation, and is suitable for the rapid detection of methyl parathion in various foods. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 : Surface morphology of the GR@TA-Ag@MIH electrode modification material prepared in Example 1 of the present invention at different magnifications;
[0032] Figure 2 : A is the CV curve of GR@TA-Ag@MIH / GCE of the present invention at different scan rates in 100uM methyl parathion; B is the relationship between the peak potential and the logarithm of the scan rate;
[0033] Figure 3: A is the DPV curve of methyl parathion solution of GR@TA-Ag@MIH / GCE of the present invention at different pH values; B is the relationship between the peak potential and different pH values;
[0034] Figure 4 : DPV curves of GCE, GR@TA-Ag@MIH / GCE, and GR@TA-Ag@NIH / GCE in 100uM methyl parathion solution;
[0035] Figure 5 : The absorbance of TA-Ag at the ultraviolet absorption wavelength of 652nm changes with time;
[0036] Figure 6 :A is the DPV curve of methyl parathion at different concentrations; B is the working curve of methyl parathion;
[0037] Figure 7 : The current values measured by GR@TA-Ag@MIH / GCE and GR@TA-Ag@NIH / GCE when the same concentrations of glyphosate, acephate and trichlorfon were added to the 50uM methyl parathion solution. DETAILED DESCRIPTION
[0038] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0039] As described in the background technology, the traditional separation and analysis methods reported in the literature for methyl parathion mainly include chromatography and chromatography-mass spectrometry for qualitative and quantitative detection, but the equipment used in the above detection methods is expensive, the analysis time is long, and complex sample pretreatment technology is required. In the prior art, although there are also reports on the determination of methyl parathion using electrochemical methods, most of the methods for preparing the modified materials of existing photoelectrochemical sensors are complicated, and compounds with similar structures can also have current response at the same potential, thereby interfering with the detection of methyl parathion, reducing the accuracy and specificity of the detection.
[0040] Based on this, the purpose of the present invention is to provide an electrochemical sensor capable of sensitively and specifically detecting methyl parathion and a detection method thereof. In order to achieve sensitive and specific detection of methyl parathion, an electrochemical sensor capable of sensitively detecting methyl parathion was constructed using a GR@TA-Ag@MIH modified electrode as a working electrode.
[0041] The CV curves of the working electrode (GR@TA-Ag@MIH / GCE) of the present invention at different scan rates in 100uM methyl parathion and the linear relationship between the peak potential and the logarithm of the scan rate. Figure 2 (A) It can be seen that the peak current increases with the increase of scanning rate, and the peak potential moves toward the negative potential direction with the increase of scanning rate. Figure 2 The linear equation of peak potential and scan rate logarithm obtained in (B) is E pc (V) = 0.0265logv(Vs -1 )-0.0829. According to Lavirons equation:
[0042]
[0043] Among them, A is a constant related to the standard electrode potential; α is the transfer coefficient; n is the number of electron transfers in the diffusion-controlled process; R, T and F are the gas constant, temperature and Faraday constant, respectively. The slope of the straight line should be 2.303RT / αnF. The number of electron transfers α = 0.5, and n is about 4 calculated by the obtained linear equation. Therefore, it can be inferred that the oxidation reaction of methyl parathion is a reaction involving 4 electrons.
[0044] The present invention further explores the oxidation mechanism of methyl parathion by investigating the relationship between the peak potential and pH of GR@TA-Ag@MIH / GCE in 100uM methyl parathion solutions prepared at different pH values. Figure 3 (A) is the DPV curve of GR@TA-Ag@MIH / GCE in 100uM methyl parathion solution prepared at different pH values. It can be seen from the figure that as the pH gradually increases, the peak potential value gradually moves toward the negative potential direction. According to the relationship between the peak potential and pH, the linear relationship between the two is Ep(V)=-0.0631pH+1.3643( Figure 2 (B)). However, the theoretical value of the slope of the linear relationship between Ep and pH is 59mV. This result shows that the number of protons and electrons involved in the oxidation reaction of methyl parathion is equal. Combined with the previous results, 4 electrons are involved in the oxidation reaction of methyl parathion. Finally, it can be inferred that the oxidation reaction of methyl parathion is participated by 4 electrons and 4 protons.
[0045] Figure 4The DPV curves of different modified electrodes in 100uM methyl parathion solution. It can be seen from the figure that after the GCE surface is modified with GR@TA-Ag@MIH, the oxidation peak current value of methyl parathion increases. Compared with GCE, the peak current value of GR@TA-Ag@MIH increases significantly, and the current value of GR@TA-Ag@MIH is greater than that of Gr / TA-Ag@NIH. The GR@TA-Ag@MIH composite material has good conductivity after adding graphene, and the added metal ions improve the conductivity of the composite material; molecular imprinting can realize the specific recognition of methyl parathion by electrochemical sensors, eliminating the interference of oxidation peaks of compounds with similar structures at the same potential, thereby improving the accuracy of detection; a TA-Ag dual catalytic system is constructed, so that the formation of hydrogel does not require high-temperature heating, and free radicals are rapidly polymerized at room temperature; the self-adhesiveness of the hydrogel is utilized to improve the binding force between GR@TA-Ag@MIH and the electrode, and at the same time, the adsorption capacity of methyl parathion is improved. The combination of the above multiple advantages significantly improves the oxidation peak current value of methyl parathion, giving the sensor higher sensitivity and stability. The method of the present invention achieves a minimum detection limit of 0.1umol / L for methyl parathion, achieving highly sensitive and specific detection of methyl parathion.
[0046] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.
[0047] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.
[0048] The synthesis method of Gr / TA-Ag@NIH / GCE used in the present invention is compared with the synthesis of GR@TA-Ag@MIH / GCE in Example 1, except that the template molecule methyl parathion is not added, the other synthesis steps are the same.
[0049] Example 1: Preparation of GR@TA-Ag@MIH electrode modified material:
[0050] (1) Dissolve 20 mg of tannic acid (TA) in 10 mL of deionized water, stir magnetically for 15 min, then add Tris solution (1 M) to adjust the pH to 8.0, add 20 mg of AgNO3, stir evenly, and obtain a TA-Ag solution;
[0051] (2) 40 mg of graphene (GR) was dissolved in 10 mL of TA-Ag solution to form a Gr@TA-Ag suspension.
[0052] (3) 10 mL of Lgr@TA-Ag suspension was added to 10 mL of a mixed solution containing acrylamide (AM), ammonium persulfate (APS) and methyl parathion (MP), wherein the mass percentage of acrylamide was 20%, the mass percentage of ammonium persulfate was 0.2%, and the mass percentage of methyl parathion was 0.003%;
[0053] The mixture was stirred magnetically for 15 min to react. After the reaction, the precipitate was eluted with a methanol-acetic acid mixed solution (the volume ratio of methanol to acetic acid was 8:2) until no methyl parathion was present. The methanol-acetic acid mixed solution was then washed away with deionized water to prepare the GR@TA-Ag@MIH electrode modified material.
[0054] Figure 1 This is the surface morphology of the GR@TA-Ag@MIH electrode modified material prepared in Example 1. Figure 1 It can be seen that the hydrogels are connected to the polymers through multiple non-covalent bonds to form a cross-linked network structure, indicating that the hydrogel synthesis was successful.
[0055] Example 2: Preparation of GR@TA-Ag@MIH electrode modification material:
[0056] (1) Dissolve 10 mg of tannic acid (TA) in 5 mL of deionized water, stir magnetically for 15 min, then add Tris solution (1 M) to adjust the pH to 8.0, add 10 mg of AgNO3, stir evenly, and obtain a TA-Ag solution;
[0057] (2) 30 mg of graphene (GR) was dissolved in 5 mL of TA-Ag solution to form a Gr@TA-Ag suspension.
[0058] (3) 20 mL of Lgr@TA-Ag suspension was added to 10 mL of a mixed solution containing acrylamide (AM), ammonium persulfate (APS) and methyl parathion (MP), wherein the mass percentage of acrylamide was 20%, the mass percentage of ammonium persulfate was 0.2%, and the mass percentage of methyl parathion was 0.003%;
[0059] The mixture was stirred magnetically for 15 min to react. After the reaction, the precipitate was eluted with a methanol-acetic acid mixed solution (the volume ratio of methanol to acetic acid was 8:2) until no methyl parathion was present. The methanol-acetic acid mixed solution was then washed away with deionized water to prepare the GR@TA-Ag@MIH electrode modified material.
[0060] Example 3: Preparation of GR@TA-Ag@MIH electrode modification material:
[0061] (1) 30 mg of tannic acid (TA) was dissolved in 15 mL of deionized water, and magnetically stirred for 15 min. Then, Tris solution (1 M) was added to adjust the pH value to 8.0, and 30 mg of AgNO3 was added and stirred to obtain a TA-Ag solution.
[0062] (2) 50 mg of graphene (GR) was dissolved in 15 mL of TA-Ag solution to form a Gr@TA-Ag suspension.
[0063] (3) 30 mL of Lgr@TA-Ag suspension was added to 10 mL of a mixed solution containing acrylamide (AM), ammonium persulfate (APS) and methyl parathion (MP), wherein the mass percentage of acrylamide was 20%, the mass percentage of ammonium persulfate was 0.2%, and the mass percentage of methyl parathion was 0.003%;
[0064] The mixture was stirred magnetically for 15 min to react. After the reaction, the precipitate was eluted with a methanol-acetic acid mixed solution (the volume ratio of methanol to acetic acid was 8:2) until no methyl parathion was present. The methanol-acetic acid mixed solution was then washed away with deionized water to prepare the GR@TA-Ag@MIH electrode modified material.
[0065] Experimental Example 1: Nanozyme activity of TA-Ag
[0066] The activity of the TA-Ag nanozyme prepared in Example 1 was subjected to TMB colorimetry to confirm the catalase activity of the TA-Ag nanozyme. The TA-Ag solution prepared in Example 1 is the TA-Ag nanozyme.
[0067] Test method: Prepare 0.1mM TMB solution, take 200uTMB solution, add 1.5mL acetic acid-sodium acetate buffer solution (0.2M, pH=3.6), add 100uL H2O2, and finally add 100uL TA-Ag, which will change TMB from colorless to blue. Use UV-visible spectrophotometer to measure absorbance at 653nm, and draw a curve of absorbance change at 652nm over time, measuring every 20s, and the total reaction time is 200s ( Figure 5 ).
[0068] The TA-Ag nanozyme prepared by the present invention contains a phenol-quinone redox pair on the outer surface, which continuously transfers electrons to peroxides. The Ag nanoparticles are further activated by the quinone on the outer layer to continuously provide electrons to maintain the redox activity of the phenol-quinone pair. In addition, the TA-Ag nanozyme is a prerequisite for constructing a TA-Ag dual catalytic system, which can effectively catalyze the self-coagulation of hydrogels without external stimulation. The catechol groups on TA can reduce silver ions to silver nanoparticles, and are converted into semiquinone or quinone groups through oxidation of silver ions; the corresponding semiquinone or quinone groups and silver ions activate APS to generate sulfate radicals, thereby accelerating the free radical polymerization of acrylamide monomers without the need for external energy introduction, resulting in rapid in-situ gelation of hydrogels.
[0069] Test Example 2: Detection of methyl parathion using an electrochemical sensor
[0070] The glassy carbon electrode modified with the GR@TA-Ag@MIH electrode prepared in Example 1 was used as the working electrode, the platinum electrode was used as the auxiliary electrode, and the saturated calomel electrode was used as the reference electrode;
[0071] The working electrode was prepared by the following method:
[0072] 10 μL of the GR@TA-Ag@MIH electrode modification material prepared in Example 1 was dropped onto the surface of a bare glassy carbon electrode (the diameter of the glassy carbon electrode was 5 mm) using a syringe and dried at room temperature to obtain a modified GR@TA-Ag@MIH / GCE electrode, which was the working electrode.
[0073] Test method:
[0074] (1) The saturated calomel electrode and platinum electrode of the electrochemical sensor were used as the reference electrode and auxiliary electrode, respectively, and the working electrode formed a three-electrode system. The working electrode was immersed in methyl parathion standard solutions with concentrations of 1, 5, 10, 20, 50 and 100 μmol / L in the potential window of -0.6 to 0.1 V using differential pulse voltammetry, and the corresponding current values I were recorded. P ( Figure 6 A);
[0075] (2) With the concentration of methyl parathion standard solution as the horizontal axis and the current value as the vertical axis, draw a working curve ( Figure 6 B). Calculate the content of methyl parathion in the samples corresponding to different current values according to the following formula:
[0076] I(μA)=0.0799C(μM)-0.0219;
[0077] (3) Accurately weigh 20 g of cucumber sample, add 40 mL of acetonitrile solution and vortex centrifuge, repeat extraction three times, combine the extracts and use sodium chloride to promote the separation of aqueous phase and organic phase, blow dry with nitrogen, dissolve the residue obtained after nitrogen blowing with 5 mL of 0.2 mol / L phosphate buffer solution, and filter with a 0.22 μm filter membrane to obtain a sample extract;
[0078] (4) Substitute the sample extract for the standard solution and repeat step 2. According to the above calculation formula, the concentration of methyl parathion in the medium is 4.22×10 -7 mol / L, the content of methyl parathion in cucumber was calculated to be 1.11 mg / L.
[0079] Test Example 3: Specificity test of detecting methyl parathion using the electrochemical sensor of the present invention:
[0080] In order to explore the specific recognition ability of GR@TA-Ag@MIH prepared in Example 1 to methyl parathion, three structural analogs of glyphosate, dipterex and acephate at the same concentration as methyl parathion were selected for selectivity test.
[0081] The solution to be tested is:
[0082] 50 μM methyl parathion solution;
[0083] A mixed solution containing glyphosate and methyl parathion, wherein the concentrations of glyphosate and methyl parathion are both 50 μM;
[0084] A mixed solution containing trichlorfon and methyl parathion, wherein the concentrations of trichlorfon and methyl parathion are both 50 μM;
[0085] A mixed solution containing acephate and methyl parathion, wherein the concentrations of acephate and methyl parathion are both 50 μM;
[0086] Figure 6 is the peak current value of GR@TA-Ag@MIH / GCE and GR@TA-Ag@NIH / GCE in methyl parathion and three mixed solutions containing methyl parathion and its structural analogs; it is calculated that the imprinting factor of GR@TA-Ag@MIH / GCE in 50μM methyl parathion solution is 2.12, and GR@TA-Ag@MIH / GCE has no electrochemical response to the three structural analogs of glyphosate, trichlorfon and acephate alone, so in the methyl parathion solution containing glyphosate, trichlorfon and structural analogs of acephate, the calculated imprinting factors are 2.05, 1.71 and 2.14, respectively.
[0087] In the mixed solution, the molecular imprinting factor is about twice that of the non-molecular imprinting, and the current response values are almost the same, indicating that in the mixed solution of structural analogs, there is almost no current response for molecular imprinting and non-molecular imprinting. The imprinting factor is about twice, indicating that the imprinting factor in the presence of structural analogs is similar to the imprinting factor in the single methyl parathion solution, so it can be shown that the material has the ability to specifically recognize methyl parathion. It can be seen that GR@TA-Ag@MIH / GCE only has the ability to specifically recognize methyl parathion.
[0088] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A GR@TA-Ag@MIH electrode modification material, characterized in that: Prepared by the following method: (1) Dissolve tannic acid in deionized water, add Tris solution to adjust the pH to 7.5-8.5, then add AgNO3 and stir to obtain TA-Ag solution; (2) dissolving graphene in TA-Ag solution to form GR@TA-Ag suspension; (3) The GR@TA-Ag suspension was added to a mixed solution containing acrylamide, ammonium persulfate and methyl parathion, stirred for 5-15 minutes, and washed after the reaction to obtain the GR@TA-Ag@MIH electrode modified material.
2. The GR@TA-Ag@MIH electrode modification material according to claim 1, characterized in that: In step (1), the ratio of the added amount of tannic acid and deionized water is (1-3) mg: (0.5-1.5) mL; and the concentration of the Tris solution is 0.8-1.5 M.
3. The GR@TA-Ag@MIH electrode modification material according to claim 1, characterized in that: In step (1), the mass ratio of AgNO3 and tannic acid is (1-3): (1-3).
4. The GR@TA-Ag@MIH electrode modification material according to claim 1, characterized in that: In step (2), the material-liquid ratio of graphene and TA-Ag solution is (3-5) mg: (0.5-1.5) mL.
5. The GR@TA-Ag@MIH electrode modification material according to claim 1, characterized in that: In step (3), the volume ratio of the GR@TA-Ag suspension and the mixed solution is (1-3): (1-3).
6. The GR@TA-Ag@MIH electrode modification material according to claim 1, characterized in that: In step (3), in the mixed solution, the mass percentage of acrylamide is 15-25%; the mass percentage of ammonium persulfate is 0.1-0.3%; and the mass percentage of methyl parathion is 0.002-0.004%.
7. Use of the GR@TA-Ag@MIH electrode modification material according to any one of claims 1 to 6 in the preparation of an electrochemical sensor for detecting methyl parathion.
8. An electrochemical sensor, characterized in that The electrochemical sensor uses a glassy carbon electrode modified with the GR@TA-Ag@MIH electrode modification material according to any one of claims 1 to 6 as a working electrode, a platinum electrode as an auxiliary electrode, and a saturated calomel electrode as a reference electrode.
9. The electrochemical sensor according to claim 8, characterized in that The working electrode is prepared by the following method: The GR@TA-Ag@MIH electrode modification material was drop-coated onto the surface of the bare glassy carbon electrode using a syringe and allowed to dry to obtain a modified GR@TA-Ag@MIH@GCE electrode, which was the working electrode.
10. A method for detecting methyl parathion using the electrochemical sensor according to claim 8 or 9, characterized in that: The following steps are involved: (1) The working electrode, reference electrode and auxiliary electrode in the electrochemical sensor constitute a three-electrode system. The working electrode is immersed in different concentrations of methyl parathion standard solution and incubated in the potential window range of -0.6 to 0.1 V using differential pulse voltammetry, and the corresponding current value I is recorded. P ; With the concentration of methyl parathion standard solution as the abscissa and the current value I as the ordinate, draw a working curve; (2) using the working curve drawn in step (1) to detect the content of methyl parathion in the pre-treated analyte; Preferably, in step (2), the pretreatment method of the analyte is: repeatedly extracting the analyte with acetonitrile by vortex centrifugation for 2 to 4 times, promoting the separation of the aqueous phase and the organic phase with sodium chloride, combining the extracts and blowing them dry with nitrogen, dissolving the residue obtained after nitrogen blowing with phosphate buffer solution, and filtering to obtain the sample extract.
Citation Information
Patent Citations
Methyl-parathion molecularly-imprinted electrochemical sensor and preparation method thereof
CN103675050A
Preparation method and application of double-electric-field driving sensor
WO2023212991A1